2014
DOI: 10.1002/ijc.28829
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II study of apatinib, a novel VEGFR inhibitor in heavily pretreated patients with metastatic triple-negative breast cancer

Abstract: Apatinib is an oral, highly potent tyrosine-kinase inhibitor targeting VEGFR2. Phase I study showed the recommended dose of 750 mg/day with substantial antitumor activity. This phase II study aims to evaluate the optimum dose level for the efficacy and safety of apatinib monotherapy in heavily pretreated patients with metastatic triple negative breast cancer (mTNBC) in China. Phase IIa was first performed among 25 patients previously treated with anthracycline and/or taxane. All patients received apatinib 750 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
286
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 242 publications
(304 citation statements)
references
References 51 publications
13
286
2
Order By: Relevance
“…Lung cancer is typically a malignant cancer with sufficient blood supply that can secrete lots of VEGF during tumor growth (16). Expression of VEGF mRNA and protein in lung cancer samples are 3-7 higher than normal renal tissues (16). In the present study, tetrandrine significantly induced the protein expression of PARP and Bax, suppressed p-Akt protein levels and increased VEGF expression in A549 cells.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Lung cancer is typically a malignant cancer with sufficient blood supply that can secrete lots of VEGF during tumor growth (16). Expression of VEGF mRNA and protein in lung cancer samples are 3-7 higher than normal renal tissues (16). In the present study, tetrandrine significantly induced the protein expression of PARP and Bax, suppressed p-Akt protein levels and increased VEGF expression in A549 cells.…”
Section: Discussionmentioning
confidence: 48%
“…VEGF is the most effective vasculogenesis-associated factor (16). VEGF is highly expressed in ovarian cancer, breast carcinoma, gastric carcinoma and urinary bladder carcinoma (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase II trials in different settings with motesanib, pazopanib, axitinib, cediranib and vandetanib in breast cancer patients showed no clinical efficacy while toxicity was present in most of the studies Rugo et al, 2011;Boer et al, 2012;Hyams et al, 2013;Johnston et al, 2013). Two other phase I trials and one phase II trial with nintedanib, tivozanib and apatinib respectively showed partial response or pathological response up to 50% of the patients (Mayer et al, 2013;Hu et al, 2014;Quintela-Fandino et al, 2014). Further studies with TKIs targeting VEGFR are ongoing (Table 1).…”
Section: Vegf-a -Clinical Datamentioning
confidence: 92%
“…Additionally, levels of VEGF in plasma may be a biomarker of response to anti-angiogenic therapy20. Despite recent setbacks in the use of anti-angiogenic therapy in breast cancer, the importance of VEGF in tumor progression, and its potential targeting for treatment remains undeniable21222324.…”
mentioning
confidence: 99%